Global knowledge mapping of receptor activator of nuclear factor kappa-B ligand in osteoporotic fractures: a bibliometric analysis (2001–2024) - Lu, Shuai; Shen, Huaishuang; Li, Minjuan; Luo, Yiming; Sun, Hao; Zhao, Xian; Chen, Jianming; Bai, Ruifeng; Han, Pengli; Zha, Yejun; Jiang, Xieyuan (Frontiers in Molecular Biosciences, 2025)
BackgroundReceptor activator of nuclear factor kappa-B ligand (RANKL) plays a critical role in bone metabolism and the pathogenesis of osteoporotic fractures. This study aims to conduct a bibliometric analysis of global research pertaining to RANKL and osteoporotic fractures to identify key trends, influential studies, and collaborative networks.MethodsA literature search was conducted to identify articles found in the Web of Science Core Collection database regarding RANKL and osteoporotic fractures from 2001 to 2024. A bibliometric analysis was performed using VOSviewer, CiteSpace, and R 4.3.3 for the publication volume, country and institution contributions, journal impact, author influence, and research hotspots.ResultsA total of 214 articles were analyzed. Publication rates have steadily increased, with a peak of 21 papers in 2020. The U.S., China, and South Korea were the top contributing countries, and leading institutions included Harvard University and Dankook University. The Journal of Bone and Mineral Research, Osteoporosis International, and Bone were the journals of highest impact. At the level of authors, Heiss–Christian published the highest number and Christiansen–Claus had the strongest citation impact (1,368 citations). Research evolved from basic biological mechanisms (2001–2010) through clinical applications (2011–2017) to recent renewed interest in fundamental RANKL biology (2018–2024). Key research hotspots included postmenopausal osteoporosis, bone mineral density, and osteoclast differentiation, with emerging focus on RANKL’s role beyond skeletal metabolism.ConclusionThis bibliometric analysis provides a comprehensive overview of RANKL research in osteoporotic fractures, highlighting key priorities for future investigation. Future studies should prioritize understanding RANKL’s broader physiological roles, developing better predictive markers, and optimizing personalized treatment strategies.